The perceived impact of digital disruption on video entertainment viewership in South Africa - Behari, Deon Krishen (University of the Witswatersrand, Johannesburg, 2023)
This thesis investigates the perceived impact of digital disruption on video entertainment viewership in South Africa. The traditional television industry has been undergoing significant changes globally, driven by digital technological advancements and the emergence of alternative distribution services such as video streaming. This disruption has resulted in transformations in traditional TV viewership patterns, posing challenges to the viability and sustainability of the existing broadcast industry. The research objectives focus on understanding the current state of traditional TV viewership and the adoption of over-the-top (OTT) video streaming services in South Africa. The study explores the relationships between the cost, convenience, and content of OTT services and the frequency of traditional TV viewership. The study employs an online survey questionnaire as the method of data collection, enabling efficient targeting of a diverse and dispersed sample base. The key findings indicate a decline in traditional TV viewership in South Africa, attributed to the increasing popularity of OTT platforms. The research also highlights the importance of content curation, recommendation algorithms, and cost affordability in driving OTT service adoption. The implications of the study suggest the need for broadcasters to refocus their strategies and policymakers to consider the challenges and opportunities presented by the digital transition. The findings underscore the significance of tailoring content and platform strategies to different age groups and socioeconomic backgrounds. This study contributes valuable insights into the South African context, considering its unique cultural, societal, economic, and historical factors. It provides actionable recommendations for stakeholders in the media, broadcasting, and video entertainment industries in South Africa
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business
Keywords: Over-the-top; Platforms; Online; Digital disruption; Video-entertainment; Watching; Video-on-demand; SDG-9: Industry, innovation and infrastructure